Brain stimulation modulates the autonomic nervous system, rating of perceived exertion and performance during maximal exercise. Issue 18 (27th February 2013) - Okano, Alexandre Hideki; Fontes, Eduardo Bodnariuc; Montenegro, Rafael Ayres; Farinatti, Paulo de Tarso Veras; Cyrino, Edilson Serpeloni; Li, Li Min; Bikson, Marom; Noakes, Timothy David
Abstract : Background: The temporal and insular cortex (TC, IC) have been associated with autonomic nervous system (ANS) control and the awareness of emotional feelings from the body. Evidence shows that the ANS and rating of perceived exertion (RPE) regulate exercise performance. Non-invasive brain stimulation can modulate the cortical area directly beneath the electrode related to ANS and RPE, but it could also affect subcortical areas by connection within the cortico-cortical neural networks. This study evaluated the effects of transcranial direct current stimulation (tDCS) over the TC on the ANS, RPE and performance during a maximal dynamic exercise. Methods: Ten trained cyclists participated in this study (33±9 years; 171.5±5.8 cm; 72.8±9.5 kg; 10–11 training years). After 20-min of receiving either anodal tDCS applied over the left TC (T3) or sham stimulation, subjects completed a maximal incremental cycling exercise test. RPE, heart rate (HR) and R–R intervals (as a measure of ANS function) were recorded continuously throughout the tests. Peak power output (PPO) was recorded at the end of the tests. Results: With anodal tDCS, PPO improved by ∼4% (anodal tDCS: 313.2±29.9 vs 301.0±19.8 watts: sham tDCS; p=0.043), parasympathetic vagal withdrawal was delayed (anodal tDCS: 147.5±53.3 vs 125.0±35.4 watts: sham tDCS; p=0.041) and HR was reduced at submaximal workloads. RPE also increased more slowly during exercise following anodal tDCS application, but maximal RPE and HR values were not affected by cortical stimulation. Conclusions: The findings suggest that non-invasive brain stimulation over the TC modulates the ANS activity and the sensory perception of effort and exercise performance, indicating that the brain plays a crucial role in the exercise performance regulation.